The “CHRISTIAN NATIONALISM” of Nichifor Crainic reflected in his work from the 4th decade of the 20th century - MORARIU, Iuliu Marius (Presa Universitară Clujeană, 2020)
This presentation will be dedicated to the way how the Christian-nationalist conception of Romanian theologian, philosopher and politician Nichifor Crainic (1889-1972) is reﬂected in his publicist work from the 4th decade of the 20th century.